Comparative genomics of Synechococcus and proposal of the new genus Parasynechococcus - Felipe Coutinho; Diogo Antonio Tschoeke; Fabiano Thompson; Cristiane Thompson (PeerJ, 2016)
Synechococcus is among the most important contributors to global primary productivity. The genomes of several strains of this taxon have been previously sequenced in an effort to understand the physiology and ecology of these highly diverse microorganisms. Here we present a comparative study of Synechococcus genomes. For that end, we developed GenTaxo, a program written in Perl to perform genomic taxonomy based on average nucleotide identity, average amino acid identity and dinucleotide signatures, which revealed that the analyzed strains are drastically distinct regarding their genomic content. Phylogenomic reconstruction indicated a division of Synechococcus in two clades (i.e. Synechococcus and the new genus Parasynechococcus), corroborating evidences that this is in fact a polyphyletic group. By clustering protein encoding genes into homologue groups we were able to trace the Pangenome and core genome of both marine and freshwater Synechococcus and determine the genotypic traits that differentiate these lineages.